Morules in endometrial carcinoma and benign endometrial lesions differ from squamous differentiation tissue and are not infected with human papillomavirus. Issue 9 (27th August 2004) - Chinen, K; Kamiyama, K; Kinjo, T; Arasaki, A; Ihama, Y; Hamada, T; Iwamasa, T
Abstract : Background: Squamous differentiation/squamous metaplasia is often associated with endometrial adenocarcinoma and benign lesions, such as endometrial hyperplasia and chronic endometritis. Morules have distinct histological characteristics, and are referred to as squamous metaplasia or squamoid metaplasia. Aim: To focus on the histological characteristics of morules and clarify the difference between morules and squamous differentiation. Materials/Methods: Twenty endometrioid carcinomas with morules or squamous differentiation, five adenosquamous carcinomas, and eight non-carcinomatous endometrial lesions with morules were investigated. Numerous antibodies for epithelial membrane antigen (EMA), involucrin, cytokeratins, neuropeptides, and oncofetal antigens were used for immunohistochemistry. In situ hybridisation and polymerase chain reaction were used to detect human papillomavirus (HPV). Results: The morules observed were uniform cell clusters, with no squamous differentiation. They were immunonegative for epithelial antigens including involucrin, EMA, and cytokeratins, but were positive for neurone specific enolase. A few morules were immunopositive for acetylcholine esterase, and one case was positive for somatostatin; neither oncofetal nor proliferative cell markers, including blood group A, B, and AB, or other neuropeptides were demonstrated in the morules. HPV DNA was not found in either the morules in the carcinomas or in the benign lesions. However, true squamous differentiation tissue in four endometrioid carcinomas and two adenosquamous carcinomas was HPV positive using in situ hybridisation. Conclusion: Morules are histologically distinct from squamous metaplasia/squamous differentiation tissue. Morules are thought to be neuroectodermal-like cell clusters, and are not infected with HPV. In contrast, some of the true squamous differentiation tissue was associated with HPV infection.